Suppressive Effects of Imidapril on Th1- and Th2-Related Chemokines in Monocytes. (1st October 2011) - Tsai, Ming-Kai; Jan, Ren-Long; Lin, Ching-Hsiung; Kuo, Chang-Hung; Yang, San-Nan; Chen, Huan-Nan; Huang, Ming-Yii; Hung, Chih-Hsing
Abstract : Background: Angiotensin-converting enzyme inhibitors (ACEIs) are used to control hypertension and are superior to other antihypertensive agents in protecting the progressive deterioration of autoimmune-related nephritis. An imbalance of T helper 1 (Th1)/Th2 is thought to contribute to the pathogenesis of autoimmune diseases and their related glomerulonephritis. I-309 is a Th2-related chemokine involved in the recruitment of Th2 cells toward Th2-related inflammation. Tumor necrosis factor α (TNF-α) and Th1-related chemokines, interferon-inducible protein 10 (IP-10)/CXCL10 are also involved in autoimmune glomerulonephritis. However, the modulatory effects and the mechanisms of ACEIs on TNF-α and Th1- and Th2-related chemokines in monocytes remain poorly defined. Objective: We investigated the effects of imidapril and perindopril, 2 ACEIs, on the expression of IP-10, I-309, and TNF-α in human monocytes and also the associated intracellular mechanism. Results: Imidapril and perindopril significantly downregulated lipopolysaccharide (LPS)-induced TNF-α, I-309, and IP-10 in THP-1 cells and human primary monocytes. All 3 mitogen-activated protein kinase inhibitors suppressed LPS-induced TNF-α and I-309 expression in human primary monocytes. Only extracellular signal-regulated kinases and c-Jun N-terminal kinases (JNK) mitogen-activated protein kinase inhibitors suppressed LPS-induced IP-10 expression. Lipopolysaccharide-induced mitogen-activated protein kinase kinase 4 (MKK4), p-JNK, and c-Jun expression in human primary monocytes was suppressed by imidapril. Conclusions: These data demonstrate that ACEI is effective in downregulating LPS-induced TNF-α, I-309, and IP-10, which play important roles in the pathogenesis of inflammation. Its suppressive effect on TNF-α, I-309, and IP-10 may, at least in part, involve the down-regulation of LPS-induced MKK4-JNK-c-Jun expression.